Putusan Verstek Dalam Perkara Perceraian Di Pengadilan Agama Kelas Ib Sungguminasa Perspektif Maslahah Mursalah - Amma, Ahmad; Maknun, Lu’luil; Samin, Sabri; Hamsir, Hamsir (Tasamuh: Jurnal Studi Islam, 2023)
The high number of verset rulings by the Class I B Sungguminasa Religious Court on divorce cases each year. This paper aims to describe the efforts to apply the verstek decision, the cause of the birth of the verstek decision, and the judge's consideration in determining the verstek decision in the Class I B Sungguminasa Religious Court. This research is qualitative research with a case study model. The research methods used are observation, interviews, and documentation. Researchers used observation guidelines, interview guidelines, and documentation lists as tools in this study. Techniques by data are data reduction, data presentation, conclusions, and triangulation. Data analysis is document analysis and resource person analysis. Next, the data is tested for validity using triangulation. The results showed that: 1) The Class I B Sungguminasa Religious Court had applied the verstek verdict in accordance with the procedure. Of course, it contains benefits values. 2) The verstek judgment is influenced by the absence of the defendant, the defendant or respondent is not in place or outside the jurisdiction, the defendant or respondent has no known address (occult case), and the defendant is prohibited from attending the trial. 3) The judge handed down the verdict in the Class I B Sungguminasa Religious Court through the stages of examination of files or evidence, summons, trials I and II, consideration. If the defendant or plaintiff is not present, the panel of judges will decide on the verstek decision with the option of granting, rejecting, and not accepting.